Transmission Risk on a Neonatal Intensive Care Unit: Escherichia coli versus Klebsiella pneumoniae. (29th April 2018) - Artelt, Tanja; Kaase, Martin; Bley, Ivonne; Eiffert, Helmut; Mellmann, Alexander; Küster, Helmut; Lange, Martina; Scheithauer, Simone
Abstract : Isolation precautions required for neonatal intensive care units are part of a bundle with the aim to prevent transmission, colonization, and infection with multidrug-resistant gram-negative pathogens as neonates face an increased risk of mortality and morbidity in case of infection. The following short report describes a transmission of 3MDRGN Klebsiella pneumoniae on a neonatal intensive care unit in a university hospital in Germany. This transmission occurred even though intensified infection control measures were in place, which impressively shows the importance of surveillance, outbreak management, and awareness of contributing factors regarding outbreak situations.